Associations of Zakat Scholarship Support and Islamic Financial Behavior with Academic Performance among Recipients of Four Zakat Institutions - Sindi Rahmadani; Muhammad Yafiz; Purnama Ramadani Silalahi (Tasharruf: Journal Economics and Business of Islam, 2026)
This study aims to analyze the relationship between Zakat Scholarship Support, Islamic Financial Behavior, and Academic Performance among university students receiving zakat scholarships from four zakat institutions in Medan. A quantitative cross-sectional design was employed using questionnaire data from 64 scholarship recipients, selected through proportional sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The results show that Zakat Scholarship Support has a positive and significant relationship with Academic Performance (β = 0.390, p = 0.048; f² = 0.274), while Islamic Financial Behavior also has a positive and significant relationship (β = 0.507, p = 0.001; f² = 0.464). The model explains 64.9% of the variance in Academic Performance (R² = 0.649) and demonstrates predictive relevance (Q² = 0.470). Islamic Financial Behavior shows a larger practical contribution based on its effect size. These findings indicate that both variables are relevant to the self-reported Academic Performance of zakat scholarship recipients, although the cross-sectional design does not support causal conclusions.This study suggests that integrating zakat-based financial assistance with financial literacy and behavioral coaching is a promising direction for future research and program evaluation for recipients of zakat scholarships.